2015
DOI: 10.1590/0100-67622015000500020
|View full text |Cite
|
Sign up to set email alerts
|

Trocas Gasosas E Eficiência Do Fotossistema Ii Em Plantas Adultas De Seis Espécies Florestais Em Função Do Suprimento De Água No Solo1

Abstract: RESUMO -A redução da disponibilidade hídrica causa efeitos sobre a fotossíntese e o desenvolvimento de espécies arbóreas. O objetivo deste trabalho foi avaliar as trocas gasosas e a eficiência fotoquímica do fotossistema II em plantas adultas de gonçalo-alves (Astronium fraxinifolium Schott.), guanandi (Calophyllum brasiliense Cambess.), ipê-amarelo (Handroanthus serratifolius (Vahl.), ipê-rosa (Handroanthus impetiginosa (Mart.) Matos), marupá (Simarouba amara Aubl.) e mogno (Swietenia macrophylla King.) culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
2
20
0
4
Order By: Relevance
“…Similarly to A to gs reduced until the 14 o days after suspension of irrigation in seedlings under water deficit, remaining constant until the first P0, highlighting the relationship between gs and A. The variations in E followed the same behavior as gs, suggesting that the plants reduce water loss by transpiration through stomatal closure, according to water availability (Campelo et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly to A to gs reduced until the 14 o days after suspension of irrigation in seedlings under water deficit, remaining constant until the first P0, highlighting the relationship between gs and A. The variations in E followed the same behavior as gs, suggesting that the plants reduce water loss by transpiration through stomatal closure, according to water availability (Campelo et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
“…Stomatal closure is considered the main cause of reduced photosynthetic and transpiration rates in plants under water deficit conditions (Gonçalves et al, 2009). Campelo et al (2015) observed that E was more pronouncedly affected in dry seasons, followed by recovery during the rainy season, in Swietnia macrophylla King. and Calophyllum brasiliense Cambess.…”
Section: Discussionmentioning
confidence: 99%
“…Esses valores para as parcelas continuamente irrigadas foram 6,6% e 5,0% na camada de 0-20 cm, respectivamente, para os meses de novembro e maio. Para uma análise detalhada dos perfis de umidade na área de estudo consultar Campelo et al (2015).…”
Section: Methodsunclassified
“…O balanço entre assimilação de CO 2 e o conteúdo do elemento na folha é um importante fator que deve ser levado em consideração na análise da eficiência fotossintética de nutrientes, pois ocorre de maneira diferente nas espécies. Segundo Campelo et al (2015), para as mesmas condições deste artigo, o ipê-amarelo tem a taxa de assimilação de CO 2 afetada significativamente pelo estresse hídrico, porém, as concentrações de N e P também diminuem, equilibrando o balanço de ganho de carbono e a quantidade do nutriente na folha. Por outro lado, o gonçalo-alves tem a eficiência fotossintética pouco reduzida nas mesmas condições, porém, mantém as concentrações de N e P, conservando a A/N e A/P independentemente da disponibilidade hídrica do solo.…”
Section: Eficiência Fotossintética Do Uso De Nitrogênio E Fósforounclassified
“…The savanna thinning treatment provided an environment for herbaceous plants that favored the best use of such abiotic factors as light, temperature, and humidity by them, which improved the performance of their photosynthetic processes, especially in forage plants (Table 1). According to Campelo et al (2015), low water availability and humidity, high temperature, and/or high coverage of the woody stratum, affects the photochemical and biochemical reactions that are directly linked to stomatal closure. This increase in the savannathinned area was especially large in plants of the family Fabaceae, while in the control area this number was lower (Table 2).…”
Section: Continuationmentioning
confidence: 99%